STUDENTS’ PERCEPTION ON USING GOOGLE FORM AS A READING COMPREHENSION ASSESSMENT AT SMAN 3 BUKITTINGGI - Iwila Trisma; Arifmiboy; Melyan Melani; Loli Syafitri (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. The research was due to several problems found in the field: not all students can use the google form in an independent reading comprehension assessment, and the lack of practicality and effectiveness of students in using the google form as a reading assessment. The research is aimed to find out students' perceptions of using Google Forms. This research used descriptive quantitative research. Descriptive research is a kind of research method to describe and interpret an object naturally. The instrument in this study used a questionnaire to determine students' perceptions of the use of Google Forms as an assessment of reading comprehension. Data were collected from questionnaires which were distributed to each sample, besides that data analysis was carried out by identifying respondents' answers, and analyzing data. In this study, the population is all students of class X SMAN 3 Bukittinggi which consists of 3 departments amounting to 367 people. And the samples were 2 classes of Mathematics and Natural Sciences I and MIPA II whose samples used purposive sampling. Data analysis was carried out by identifying respondents' answers, calculating the percentage of each indicator, and concluding. The results of this study indicate that students' perceptions using google form as a reading comprehension assessment found in the practicality indicator with a percentage of 86.80% very practical, then the effectiveness indicator 82.81% is very effective. It can be concluded that students have a good perception of the use of Google Forms as an assessment of reading comprehension.